2018
DOI: 10.24839/2325-7342.jn23.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Media on Perceptions of Violence as a Function of Trait Aggression and Athletic Status

Abstract: DEDICATION STATEMENT This issue is dedicated to JON GRAHE, PhD (2016-17 Psi Chi President, Pacific Lutheran University), who first introduced Psi Chi Journal to the Open Science Badges program and later proposed the topic of this special issue. Over the years, Jon has worked tirelessly to create collaborative research opportunities for Psi Chi students, and supported the Journal's transition to an Open Access publication. ABOUT PSI CHI Psi Chi is the International Honor So ci ety in Psychology, found ed in 192… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous studies over the course of 50 years have confirmed that violent media content (e.g., spreading a harmful rumor about others) increases aggressive and antisocial behavior (Anderson et al., 2007; Branley & Covey, 2017; Gross & Mendoza, 2018; Lam et al., 2013). The association between exposure to violent media and aggressive behavior has been reconfirmed in experimental studies (e.g., Saleem et al., 2012), a meta-analysis (e.g., Greitemeyer & Mügge, 2014), and longitudinal studies (e.g., Huesmann et al., 2003).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies over the course of 50 years have confirmed that violent media content (e.g., spreading a harmful rumor about others) increases aggressive and antisocial behavior (Anderson et al., 2007; Branley & Covey, 2017; Gross & Mendoza, 2018; Lam et al., 2013). The association between exposure to violent media and aggressive behavior has been reconfirmed in experimental studies (e.g., Saleem et al., 2012), a meta-analysis (e.g., Greitemeyer & Mügge, 2014), and longitudinal studies (e.g., Huesmann et al., 2003).…”
Section: Introductionmentioning
confidence: 85%
“…However, such a method may not accurately reflect one’s real attitude regarding cyber violence due to the attitude regarding social desirability. However, methods in which vignettes and photographs that describe situations of fictional violence are presented and in which the participants’ responses are measured may more accurately reflect their perception of cyber violence (Gross & Mendoza, 2018; Kret & de Gelder, 2013). Therefore, in future studies, the moderating effect of the perception of cyber violence should be re-verified through the use of various vignettes and photographs.…”
Section: Discussionmentioning
confidence: 99%
“…Brutal Actions The study by Gross and Mendoza (2018) on media exposure to violence as a function of trait aggression had shown that individuals who have been exposed to many violent media would have stable learning of aggression that has contributed to their perception. The brutal act in the 'You' drama series was perceived by the majority of informants as reality.…”
Section: Bmentioning
confidence: 99%